THE INFLUENCE OF LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY THROUGH COMMUNICATION AS A MEANS INTERVENING VARIABLES IN EXTENSION CENTER AGRICULTURE IN BIREUEN DISTRICT - Raisya Nazira; Yusniar; Ibrahim Qamarius; Likdanawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the influence of leadership and work environment on employee productivity through communication as an intervening variable at the Agricultural Extension Center in Bireuen Regency. The independent variables in this study are leadership and work environment, the dependent variable is employee productivity, and the intervening variable is communication. This study uses a quantitative method, collecting data using a questionnaire containing questions and statements distributed to all employees at the Agricultural Extension Center. The scoring technique uses a Likert scale. This study was conducted at the Agricultural Extension Center in Gandapura, Kuta Blang, and Peusangan Districts with a total of 108 respondents. The sampling method used in this study was saturated sampling, where the entire population was sampled, resulting in a total sample of 108 respondents. This study used multiple linear regression analysis with SPSS (Statistical Program for Social Science). The results of the study indicate that leadership and the work environment have a positive and significant influence on communication and directly impact employee productivity. Furthermore, communication has been shown to significantly mediate the influence of leadership and the work environment on productivity. These findings indicate that improving leadership quality and a conducive work environment, coupled with effective communication, can optimally boost employee productivity. This research is expected to serve as a reference for managers of the Agricultural Implementation Center in formulating strategies to improve employee performance.